Vibration responses of glulam beam-and-deck floors. (1st February 2018) - Ebadi, Mohammad Mehdi; Doudak, Ghasan; Smith, Ian
Highlights: Addresses vibration performance of glulam beam-and-deck floors. Experimental investigation of how design variables alter the vibration responses. Focus group subjective opinions of how floor responses to walking load. Engineering design variables effectively control the likelihood of vibration. Abstract: Floor vibration serviceability problems can exist for floors constructed from low mass-to-stiffness engineered-wood products. This paper addresses responses of beam-and-deck floors constructed using glued-laminated-timber (glulam) products. Such floors have widely spaced parallel beams supporting flat wise oriented deck elements and are a relatively new construction option for floors having spans up to about 10 m. The primary focus of discussion here is the experimental investigation of how design variables like span, support arrangement, beam spacing and the addition of non-structural topping materials alter vibration responses of floors. Focus group opinions of acceptability of motions of floors resulting from walking footfall impacts were collected as an indication of the practicality of using engineering design decisions to control vibration of beam-and-deck floors. Collected opinions support the premise that dynamic motions of floors can be controlled in desired ways using practical engineering design methods. However, it was also apparent from the data that suitable methods need to be ones specifically calibrated to suit beam-and-deck floors rather than those applied to other types of low mass-to-stiffness engineered-wood products. No attempt is made to propose new vibration serviceability performances criteria or design methods. This is because it would conflict with ongoing international efforts to create criteria and methods that apply across a wider range of floor construction technologies.